2010
DOI: 10.1530/eje-09-0436
|View full text |Cite
|
Sign up to set email alerts
|

Should anterior pituitary function be tested during follow-up of all patients presenting at the emergency department because of traumatic brain injury?

Abstract: Context: A wide range (15-56%) of prevalences of anterior pituitary insufficiency are reported in patients after traumatic brain injury (TBI). However, different study populations, study designs, and diagnostic procedures were used. No data are available on emergency-department-based cohorts of TBI patients. Objective: To assess the prevalence of pituitary dysfunction in an emergency-department-based cohort of TBI patients using strict endocrinological diagnostic criteria. Methods: Of all the patients presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 34 publications
(114 reference statements)
1
23
0
Order By: Relevance
“…This may result in higher prevalence rates when patients with a more severe degree of trauma are included. Conversely, prevalence rates of hypopituitarism may decrease when patients with only minor traumas are included (35).…”
Section: Discussionmentioning
confidence: 99%
“…This may result in higher prevalence rates when patients with a more severe degree of trauma are included. Conversely, prevalence rates of hypopituitarism may decrease when patients with only minor traumas are included (35).…”
Section: Discussionmentioning
confidence: 99%
“…They confirmed that part of the variation indeed seemed to be caused by differences in study design, diagnostic procedures, and other confounding factors such as BMI, prohibiting simple generalization from the original studies. In general, a lower prevalence of posttraumatic hypopituitarism tended to be recorded in studies using the ITT for the evaluation of the GH reserve (Kelly et al, 2000;Klose et al, 2007a;Kokshoorn et al, 2011), and in the studies using confirmatory tests (Agha et al, 2004;Klose et al, 2007a;LealCerro et al, 2005;van der Eerden et al, 2010). Table 2 a-d illustrates the relationship between diagnostic stringency and reported prevalence of GH, ACTH, LH/FSH and TSH deficiencies.…”
Section: Prevalence Of Chronic Hypopituitarism In Tbimentioning
confidence: 97%
“…Over the last 10 years, the field has received increased attention and chronic anterior pituitary hormone deficiency has been reported with a prevalence ranging from 1% and up to 83% (Table 1). The results from most studies have suggested that persistent posttraumatic hypopituitarism might be a more common complication in TBI than previously believed, although some studies have failed to show such high occurrence rates (Kokshoorn et al, 2011;van der Eerden et al, 2010). The diversity of the reported prevalences of chronic anterior pituitary hormone deficiency is likely to be explained by differences in study populations, study designs, and diagnostic procedures.…”
Section: Prevalence Of Chronic Hypopituitarism In Tbimentioning
confidence: 98%
See 2 more Smart Citations